2009
DOI: 10.1016/j.rgg.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of Miocene sandstones in northern Iraq: constraints from framework petrography, bulk-rock geochemistry and mineral chemistry

Abstract: Modal analysis, bulk-rock geochemistry and phase chemistry of sandstones of the Miocene Fat’ha and Injana formations, northern Iraq, show that the clastics were derived from heterogeneous sources that include basic igneous and metamorphic rocks as well as older sedimentary rocks. The sandstones are generally carbonate-rich lithic arenites. Their geochemistry supports the petrographic results and indicates that they are all Fe-rich, lithic or quartz arkosic sandstones. According to geochemical data, garnets are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A homogeneous sedimentary rock that is predominately composed of microscopic radiolarian organisms (Figure 5c). This fragment is derived from radiolarian chert beds and which are considered as a weathering product of the Cretaceous Qulqula Radiolarites series, NE Iraq that is adjacent to the Sanandaj-Sirjan Zone of Iran (Al-Juboury et al, 2009).…”
Section: Petrography and Mineralogymentioning
confidence: 99%
“…A homogeneous sedimentary rock that is predominately composed of microscopic radiolarian organisms (Figure 5c). This fragment is derived from radiolarian chert beds and which are considered as a weathering product of the Cretaceous Qulqula Radiolarites series, NE Iraq that is adjacent to the Sanandaj-Sirjan Zone of Iran (Al-Juboury et al, 2009).…”
Section: Petrography and Mineralogymentioning
confidence: 99%
“…Determination of tectonic location is influenced by factors such as sedimentation, diagenesis and initial composition of sediment (Pettijohn et al, 1987;Bhatia, 1983;Chamley, 1990). Therefore, the main elements of the sand can be used to determine their tectonic position (Bhatia, 1983;Von Eynatten, 2003;Armstrong-Altrin &Verma 2005;Al-Juboury et al, 2009;Sahraeyan & Bahrami, 2012 As shown in Fig. 7, based on changes in the values of the main elements, the cranial rocks of oceanic arch islands,, continental arch islands, active continental margin, and passive margin can be separated from each other.…”
Section: Fig 4 Stratigraphic Column Of Fenced Lagoon Sedimentsmentioning
confidence: 99%
“…Tectonic Location Determination of tectonic location is influenced by factors such as sedimentation, diagenesis and initial composition of sediment (Pettijohn et al, 1987;Bhatia, 1983;Chamley, 1990). Therefore, the main elements of the sand can be used to determine their tectonic position (Bhatia, 1983;Von Eynatten, 2003;Armstrong-Altrin and Verma 2005;Al-Juboury et al, 2009;Sahraeyan and Bahrami, 2012). As shown in Fig.…”
Section: Source Rockmentioning
confidence: 99%